2012
DOI: 10.1177/0021955x12459642
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of short carbon fiber/polypropylene fine-celled foams in supercritical CO2

Abstract: This article reports an attempt to improve polypropylene fine-celled foaming with the incorporation of short carbon fibers. The carbon fibers with uniform dispersion in polypropylene matrix were obtained in reference to the way of papermaking. The composites were prepared via melt compounding in a twin-screw extruder followed by injection molding. Three concentrations of carbon fibers, 5, 15 and 25 wt.%, were used. The foaming was carried out by a batch foaming process with supercritical CO2 as the physical bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 45 publications
(50 reference statements)
0
38
1
Order By: Relevance
“…Consequently, some undissolved gases may remain trapped in the microvoids at the fiber-polymer interfaces and thus ''contribute'' to the heterogeneous nucleation effect of the fibers (see Figure 7). 23 According to Wang et al, 45 increasing the cell density with increasing FF content indicates that bubble nucleation is dominated by the heterogeneous mechanism with the addition of fibers. Thus, the enhanced heterogeneous cell nucleation related to the presence of the fibers is the main reason for the improvement in cell morphology (smaller cell sizes, higher cell densities, and lower standard deviations).…”
Section: Contentsmentioning
confidence: 98%
“…Consequently, some undissolved gases may remain trapped in the microvoids at the fiber-polymer interfaces and thus ''contribute'' to the heterogeneous nucleation effect of the fibers (see Figure 7). 23 According to Wang et al, 45 increasing the cell density with increasing FF content indicates that bubble nucleation is dominated by the heterogeneous mechanism with the addition of fibers. Thus, the enhanced heterogeneous cell nucleation related to the presence of the fibers is the main reason for the improvement in cell morphology (smaller cell sizes, higher cell densities, and lower standard deviations).…”
Section: Contentsmentioning
confidence: 98%
“…However, there are potential problems with this approach. Often the cell number density is calculated from electron microscope images of cross-sections of the foams using the equation 2,[12][13][14] …”
Section: Introductionmentioning
confidence: 99%
“…This trend was consistent with experimental data reported in the previous literature. 20 The observed structure-to-property relationship, both theoretically and experimentally, revealed that foaming would be a feasible approach to promote PMC's k eff . This is especially beneficial for the PMCs with low filler loadings, which is required to ensure good processability of the material systems.…”
Section: Effect Of Filler Content On Pmc Foam's K Effmentioning
confidence: 96%